Between Online Autonomy and Local Constraints: Spaces of Roman Catholic Women's Activity in Poland. (2nd December 2021) - Szwed, Anna
Abstract: The analysis presented in this article shows how a hybrid community combining online and offline activity generates a semi-autonomous space of women's activity, neither fully independent of the religious institution, nor entirely controlled by it. Based on results obtained over 15 months of qualitative research conducted in the Captivating (Urzekająca), conservative community of Roman Catholic women in Poland, I show that digital environments are conducive to building a community of women, a creative approach to practices, renegotiating power relations, and building a sense of agency among women, while also recognizing the authority of the Church as an institution. At the same time, I argue that relative autonomy in practising religion online is limited by the pressures experienced by women in the offline space as a result of the nature of the local Church. The article discusses the question of the relations between the online and offline space, as well as the role of the broader context for understanding conservative women's practice of religion.